Physiological stress reactivity in pediatric cancer survivors treated with chemotherapy. Issue 11 (26th July 2022) - White, Gillian W.; Rhind, Shawn G.; Nathan, Paul C.; Caterini, Jessica E.; Jones, Heather NP; Wells, Greg D.
Abstract: Children who experience early life stress demonstrate changes to their stress responses, which may modulate long‐term health. Childhood cancer presents significant stress during diagnosis, treatment, and survivorship. We hypothesized that children who have completed chemotherapy treatment for ALL will demonstrate altered hormone patterns in response to a stressor compared with healthy controls. Twelve pediatric ALL survivors and 12 healthy controls completed the Trier Social Stress Test. Salivary samples, heart rate, and self‐report ratings of stress were collected at baseline, pretest, and posttest. Between group comparison showed baseline (interleukin [IL]‐8) was significantly higher in the survivor group versus controls (survivors: 89.9, 40.1–544.9 pg ml –1 ; controls: 30.7, 5.6–241.9 pg ml –1, p = .001) as was peak (IL‐8) (survivors: 147.1, 71.6–1177.6 pg ml –1 ; controls: 75.5, 28.6–698.6 pg ml –1 ). Peak salivary alpha‐amylase (sAA) concentration was significantly lower in the survivor group (survivors: 69.3, 19.4–195.5 U ml –1 ; controls: 91.2, 27.7–213.7 U ml –1 ; p = .04). Repeated measures ANOVA revealed significant main effects for time on cortisol ( F (2.35, 50.81) = 5.9, p < .01), sAA ( F (1.56, 33.17) = 6.6, p < .01), stress ratings ( F (3.42, 88.14) = 53.4, p < .001), and heart rate ( F (8, 83) = 16.8, p < .05). Significant main effects for group were observed for IL‐8 ( F (1, 23) = 8.2, p < .01) and tumor necrosis factor‐α ( F (1, 23) = 6.8, p < .05). Significant interaction effects for group × time were found for sAA ( F (5, 106) = 2.8, p < .05). Our results indicate that childhood ALL survivors have similar responses to stress as healthy controls, but lower sympatho–adrenal–medullary reactivity. Therefore, altered stress regulation may present a pathway modulating long‐term health in this population.